Zaburzenia z pogranicza nerwicy i psychozy a zdolność do podjęcia istotnych obowiązków małżeńskich - Cierpiałkowska, Lidia (Ius Matrimoniale, 2011)
The borderline personality disorders may significantly affect the capacity to perform important marital obligations, which should be appropriately reflected by canonical procedures. Psychological models and concepts of mental disorders describe them on three levels: 1) clinically significant symptoms; 2) structures and pathological mechanisms maintaining personality organization; 3) origins, i.e. The interaction of biological, psychological and social factors. The articles aims at the presentation of borderline disorders on the descriptive level according to ICD-10 and DSM-IV-R criteria, and on the explanatory level based on Kernberg’s object relations theory. Due to this conception and clinical and scientific research conducted with the application of its assumptions, the functioning of persons with psychotic, borderline and neurotic personality organization becomes more and more understandable. The conceptions has been widely used to describe and explain the phenomena that occur in marital relationships.